Adolescent stealing : a study of the causal factors for and prevalence of stealing in New Zealand intermediate school students : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education at Massey University - Seeto, Judith Elizabeth (Massey University, 1997)
A self-report questionnaire was used to measure stealing behaviour, attitudes and values, family variables, attachment to school and past-times of peers of students at a New Zealand intermediate school. Incidence rates of stealing, gender differences and school class level differences in stealing behaviour were identified from the data and compared with those found by other researchers of general delinquent behaviour and more specific stealing behaviour. Causal factors believed to be related to delinquent behaviour were measured to determine whether they were also related to stealing behaviour and to each other, as proposed in a model of delinquent behaviour. A very high proportion of participants reported having engaged in some form of stealing, reflecting the findings of other researchers. Marked gender differences in rates of stealing were found, with boys reporting significantly higher levels of theft than girls. Year 8 students reported significantly more stealing than Year 7 students. Being male, in Year 8 at school, associating with delinquent peers, holding delinquent values and having a low level of attachment to parents were factors found to be related to higher levels of stealing behaviour. These findings are discussed in relation to various theories of delinquent behaviour.
Keywords: Juvenile delinquency; Theft; Stealing behaviour; Delinquent behaviour